ANALYSIS PACKAGE DESIGN AESTHETICS TOWARDS ON FEMALE CONSUMER BUYING DECISION OF VASELINE LOTION - Kalangi, Firsie Idelrose; Mekel, Peggy Adeline (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Now a day, so many products that already produced by company as unique as possible and creative. Packaging is the one part of product that can attract the consumer or influence the consumer buying decision. Through packaging, costumer will know about the information of product and company through the label on packaging and packaging can show the visual beauty of the product. Product that has a good package design can add value to product itself. The aim of this study is to examine the effects of package design aesthetics on female consumer buying decision of Vaseline lotions with particular emphasis on these variables: package color, instructions, typography and material. This research used quantitative method. The analytical method used was multiple linier regression analysis. The data used in this research is primary data obtain through the questionnaire. The population observed is student female of Sam Ratulangi University who using Vaseline Lotion with sample as many as 100 respondents. Result and conclusions are from all variables of package design aesthetics (Color, Instructions, Typography, and Material), not all aesthetic package design elements has a significant influence on consumer buying decision. Instruction has no significant influence and color is the most influencing variable. Therefore, the management of Vaseline Company should care about package instruction on product. Keywords: product, design elements, consumer buying decision